2006
DOI: 10.1038/modpathol.3800667
|View full text |Cite
|
Sign up to set email alerts
|

Inverted papilloma of the urinary bladder: a molecular genetic appraisal

Abstract: Inverted papilloma of urinary bladder is an uncommon urothelial neoplasm. Its relationship to urothelial carcinoma is controversial. Little is known of the genetic abnormalities of inverted papilloma. To better understand its genetics, we analyzed 39 inverted papillomas, including 36 from men and three from women, for loss of heterozygosity (LOH). We examined four polymorphic microsatellite markers located on chromosome 9q32-33(D9S177), chromosome 9p22 (IFNA), chromosome 3p14.2 (D3S1300) and chromosome 17p13.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 35 publications
4
35
0
Order By: Relevance
“…Tumors may be subdivided into trabecular and glandular variants; the latter is characterized by pseudoglandular urothelial-lined spaces or even true mucicarmine-positive secreting cells [53], and is remarkably difficult to distinguish from florid cystitis glandularis. Nonrandom X-chromosome inactivation studies have found inverted papilloma to be a clonal neoplasm arising from a single progenitor cell [60]. The incidence of LOH in inverted papilloma (8%-10%) is low compared to that of UC (29%-80%) [61][62][63][64][65][66], and the frequency of allelic loss in inverted papilloma is similar to that of normal urothelium [67], suggesting that inverted papilloma and UC arise through separate and distinct pathogenetic mechanisms.…”
Section: Inverted Papillomamentioning
confidence: 97%
“…Tumors may be subdivided into trabecular and glandular variants; the latter is characterized by pseudoglandular urothelial-lined spaces or even true mucicarmine-positive secreting cells [53], and is remarkably difficult to distinguish from florid cystitis glandularis. Nonrandom X-chromosome inactivation studies have found inverted papilloma to be a clonal neoplasm arising from a single progenitor cell [60]. The incidence of LOH in inverted papilloma (8%-10%) is low compared to that of UC (29%-80%) [61][62][63][64][65][66], and the frequency of allelic loss in inverted papilloma is similar to that of normal urothelium [67], suggesting that inverted papilloma and UC arise through separate and distinct pathogenetic mechanisms.…”
Section: Inverted Papillomamentioning
confidence: 97%
“…Infrequent LOH on 3p (8%), 9p (8%), 9q (8%), and 17p (10%) was found in a study of 39 inverted papillomas. 103 A second study, of 62 inverted papillomas, found infrequent FGFR3 mutation (9.8%) and LOH of chromosome 9 (3.9% on 9p and 13.2% on 9q). 104 In the same study, inverted growth pattern urothelial carcinomas showed higher frequencies of alterations (83.1% FGFR3 mutation; 36.4% 9q LOH), indicating that inverted papillomas are distinct from urothelial papilloma and are not obviously related to carcinomas with an inverted growth pattern.…”
Section: Molecular Pathogenesismentioning
confidence: 97%
“…This type of tumor is characterized pathologically by inverted growth of transitional epithelia with no atypia. Generally, inverted papilloma occurs more frequently in men than in women, and the most common target age is 30 to 60 years old, which is younger than bladder cancer [Sung et al, 2006b]. Although the etiological factors associated with inverted papilloma have not been 5 established, HPV-DNA has been detected in some cases of inverted papilloma [Chan et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Inverted papilloma is a rare benign urothelial tumor that develops predominantly in the bladder, and accounts for less than 1% of all urothelial neoplasms [Sung et al, 2006b]. This type of tumor is characterized pathologically by inverted growth of transitional epithelia with no atypia.…”
Section: Introductionmentioning
confidence: 99%